Relationship between the sprint and vertical jumps' power in young soccer players - C.J. Silva-Junior; A. Palma; P. Costa; P.P. Pereira-Junior; R.C.L. Barroso; R.C. Abrantes-Junior; M.A.M. Barbosa (Desafio Singular, 2011)
Muscle power, speed and acceleration are generally considered important determinants of high performance in sports. Thus, the aim of this study was to evaluate the relationships between 10- and 30-meter sprint power and vertical jump power among young soccer players. The participants of the study were 143 male soccer players from the categories Under-20 (n = 34), Under-17 (n = 43) and Under-15 (n = 66), which performed vertical jump test, 10-meter sprint test and 30-meter sprint test. The results indicated weak to moderate correlations when the absolute values of time and maximal height were compared (r = −.47 to .71). When the values of power obtained from tests were compared, moderate to strong correlations were found (r = .74 to .87). The results suggest that implementing these three tests would be important because they measure different motor skills. Moreover, the correlation between vertical jump power and 30-meter sprint power was surprisingly strong. Nevertheless, further studies are required in order to improve understanding about these power relationships.